The identification of [2-14C]2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine metabolites in humans - Malfatti, Michael A.; Kulp, Kristen S.; Knize, Mark G.; Davis, Cindy; Massengill, Joyce P.; Williams, Suzanne; Nowell, Susan; MacLeod, Stewart; Dingley, Karen H.; Turteltaub, Kenneth W.; Lang, Nicholas P.; Felton, James S. (Carcinogenesis (New York), 1999)
[2-14C]2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine ([14C]PhIP), a putative human carcinogenic heterocyclic amine found in well-done cooked meat, was administered orally to three colon cancer patients undergoing a partial colonectomy. Forty-eight to seventy-two hours prior to surgery, subjects received a 70–84 μg dose of 14C. Urine and blood were analyzed by HPLC for PhIP and PhIP metabolites. Metabolites were identified based on HPLC co-elution with authentic PhIP metabolite standards, mass spectral analysis and susceptibility to enzymatic cleavage. In two subjects, ~90% of the administered [14C]PhIP dose was eliminated in the urine, whereas in the other, only 50% of the dose was found in the urine. One subject excreted three times more radioactivity in the first 4 h than did the others. Twelve radioactive peaks associated with PhIP were detected in the urine samples. The relative amount of each metabolite varied by subject, and the amounts of each metabolite within subjects changed over time. In all three subjects the most abundant urinary metabolite was identified as 2-hydroxyamino-1-methyl-6-phenylimidazo[4,5-b]pyridine-N2-glucuronide (N-hydroxy-PhIP-N2-glucuronide), accounting for 47–60% of the recovered counts in 24 h. PhIP accounted for <1% of the excreted radiolabel in all three patients. Other metabolites detected in the urine at significant amounts were 4-(2-amino-1-methylimidazo[4,5-b]pyrid-6-yl)phenyl sulfate, N-hydroxy-PhIP-N3-glucuronide and PhIP-N2-glucuronide. In the plasma, N-hydroxy-PhIP-N2-glucuronide accounted for 60, 18 and 20% of the recovered plasma radioactivity at 1 h post PhIP dose in subjects 1, 2 and 3 respectively. Plasma PhIP was 56–17% of the recovered dose at 1 h post exposure. The relatively high concentration of N-hydroxy-PhIP-N2-glucuronide and the fact that it is an indicator of bioactivation make this metabolite a potential biomarker for PhIP exposure and activation. Determining the relative differences in PhIP metabolites among individuals will indicate metabolic differences that may predict individual susceptibility to carcinogenic risk from this suspected dietary carcinogen.